(untitled) (El Hilo de la Fabula, 2025)
This study presents a study on the language of Irpinian emigration to Argentina during the 20th century, based on interviews with members of the “I figli di Lioni” community in Santa Fe, in 2023. The aim was to analyse the interaction between Italian, dialect, and Spanish in the repertoires of those who emigrated during adolescence. The case of Marianna D’Andrea is exemplary: her testimony, shaped by family memories and migration experiences, reveals phenomena of linguistic interference, code-switching, and the persistence of dialect in emotionally charged contexts. The study highlights how migratory memory intertwines with linguistic identity and how cocoliche remains a living trace of the cultural and linguistic contact between Italy and Argentina.